Andrew Jackson--Encyclopedia of Presidents - Osinski, Alice (Chicago, IL: Childrens Press, 1986)
Summary: Traces the life of the rowdy "Hero of New Orleans" from his backwoods beginnings through his military career to his term as seventh president of the United States.
Keywords: Jackson, Andrew--1767-1845.; Presidents